2022
DOI: 10.1002/ente.202201045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of an Aromatic Sulfonate Sodium Salt for Aqueous Sodium‐Ion Battery Electrolytes

Abstract: The two‐step synthesis of sodium (2,3,5,6‐tetrafluorophenoxy) diethane sulfonate (Na‐TFP) is reported, starting from 2,3,5,6‐tetrafluorohydroquinone as the precursor. Compared with conventional aqueous electrolytes such as 0.5 m NaClO4 and Na2SO4, the 0.5 m aqueous solution of Na‐TFP provides higher ionic conductivity over a wide range of temperature (e.g., >60 mS cm−1 at 20 °C and >70 mS cm−1 at 30 °C) and a wider electrochemical stability window. Electrochemical cells with Na2VTi(PO4)3 as the positive electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This system provided better cyclic stability of 400 cycles at 2 C with a capacity retention of 90%. [80] To address the flammability issue of non-aqueous electrolytes, Colbin et al reported a fluorine-free and flame-retardant non-aqueous electrolyte using 0.38 M sodium bis(oxalato)borate (NaBOB) in triethyl phosphate (TEP) and also provided satisfactory passivation of hard carbon at low salt concentration and without the use of any additives. This electrolyte exhibited ionic conductivity of 5 mS cm −1 at room temperature and a viscosity of 2.674 mPaÁs.…”
Section: Electrolytementioning
confidence: 99%
“…This system provided better cyclic stability of 400 cycles at 2 C with a capacity retention of 90%. [80] To address the flammability issue of non-aqueous electrolytes, Colbin et al reported a fluorine-free and flame-retardant non-aqueous electrolyte using 0.38 M sodium bis(oxalato)borate (NaBOB) in triethyl phosphate (TEP) and also provided satisfactory passivation of hard carbon at low salt concentration and without the use of any additives. This electrolyte exhibited ionic conductivity of 5 mS cm −1 at room temperature and a viscosity of 2.674 mPaÁs.…”
Section: Electrolytementioning
confidence: 99%